SUSTAINABLE DEVELOPMENT IN LOW CARBON, CLEANER AND GREENER ENERGIES AND THE ENVIRONMENT - Abdeen Mustafa Omer (Universitas Mercu Buana, 2021)
The increased availability of reliable and efficient energy services stimulates new development alternatives. This article discusses the potential for such integrated systems in the stationary and portable power market in response to the critical need for cleaner energy technology. Several issues relating to renewable energies, environment, and sustainable development are examined from both current and future perspectives throughout the theme. It is concluded that green energies like wind, solar, ground source heat pumps, and biomass must be promoted, implemented, and demonstrated from the economic and/or environmental point of view. Biogas from biomass appears to have potential as an alternative energy source, potentially rich in biomass resources. The current literature is reviewed regarding the ecological, social, cultural and economic impacts of biogas technology. Finally, this article gives an overview of the present and future use of biomass as an industrial feedstock to produce fuels, chemicals and other materials. However, to be truly competitive in an open market situation, higher-value products are required. Results suggest that biogas technology must be encouraged, promoted, invested, implemented, and demonstrated, especially in remote rural areas. Anticipated future energy use patterns and consequent environmental impacts (acid precipitation, ozone depletion, greenhouse effect, or global warming) are discussed in this article. An approach is needed to integrate renewable energies in a way to meet high building performance. However, their ability to match demand is determined by adoption of one of the following two approaches: the utilisation of a capture area greater than that occupied by the community to be supplied, or the reduction of the community’s energy demands to a level commensurate with the locally available renewable resources. Adopting green or sustainable approaches to how society is run is seen as an important strategy in finding a solution to the energy problem. The key factors to reducing and controlling CO2, which is the major contributor to global warming, are the use of alternative approaches to energy generation and the exploration of how these alternatives are used today and may be used in the future as green energy sources.